Puzzle Homonim sebagai Media Pengembangan Kreativitas Siswa dalam Berbahasa - Fitakhu Khoirul Ilmiah; Duwi Andinis; Nensy Megawati Simanjuntak (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Learning media plays a very important role in the learning process, namely as a means of increasing students' understanding of the subject matter. Homonym puzzles are a learning medium that can increase students' interest in learning and also creativity, because in homonym puzzles there are various activities that require students to be active and think critically in solving problems. This research aims to describe the influence of homonym puzzles as a medium for developing students' creativity in language. This research includes qualitative research using an experimental approach. The data source used is primary data, namely students of Clear IV UPT SDN 205 Gresik. Data collection methods are through observation, tests and documentation.The results of this research show that with the presence of homonym puzzles there is a significant increase in students' understanding and development of creativity in language. This can be seen from students' ability to think critically and actively, thereby helping them to develop better language skills.